(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The development of economic terminology depends on social conditions, in this case, the transition to market relations. But at the same time, the development of vocabulary is determined by intralinguistic factors associated with the systemic nature of the language. Important changes are also taking place in the science of terms, as a result of which a new - cognitive - direction of terminology is being formed. The significance of the article lies in the fact that the composition in which it functions in the modern Uzbek language and the results of the study can be used in conducting integrated lessons, which will diversify the forms of education.